IMPROVING STUDENTS’ SKILLS IN WRITING A DESCRIPTIVE PARAGRAPH USING PEER-CORRECTION - Arielia Pachira Humarani; Nurhaedah Gailea; Eri Rahmawati (Lingua Scientia, 2023)
The research objective was to determine the improvement of students’ skills in writing a descriptive paragraph using peer-correction technique on seventh grade students at SMPN 10 Kota Serang. The quantitative research with pre-experimental method was employed in this research, and one-group pretest-posttest design was implemented. The subject of this research was 30 students of VII I class and it was chosen based on the simple random sampling technique. The result of the study shows that the mean posttest score (71.10) exceeded the mean pretest score (52.33). Furthermore, Ha is accepted. This indicates that through receiving treatment, students' writing descriptive text abilities improved. Moreover, the researcher calculated that the score of t obtained < t table (-119.751 < 2.045) and the sig. (2-tailed) < 0.05 (0.000 < 0.05). It means that Ha is accepted and Ho is rejected. It can be concluded that the Peer-Correction has an improvement on the writing skills of seventh grade students at SMPN 10 Kota Serang. Keywords: descriptive text, peer-correction, writing Skills, technique, treatment